MEWARNAI DUNIA BELAJAR ANAK DESA PAO MELALUI PENDEKATAN KREATIF DALAM PEMBELAJARAN MATEMATIKA DAN BAHASA INGGRIS DI SD LEMBANG - Putri RM, Risma Febriyanti; Ali, Andi Fazlur Rahman Ali; Ali, Rahmawati; Syafi'i, Muhammad Islah; Qura, Ummul (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
The community service program conducted by MP Ekolibrium FEB UNM, through its educational work program, aims to enhance elementary students’ motivation and understanding in Desa Pao by applying creative play-based learning in Mathematics and English subjects. The method used was a participatory approach consisting of preparation, implementation, teacher mentoring, and evaluation and reflection stages. The program was carried out over ten days involving students and accompanying teachers at SD Lembang. The results showed increased motivation, participation, and conceptual understanding among students through enjoyable and collaborative learning activities. Teachers also gained new experiences in designing creative and interactive lessons. This approach proves that game-based learning effectively creates meaningful learning experiences and can be replicated in other rural elementary schools.